Pengaruh Celebrity Endorsement, Customer Satisfaction, Viral Marketing Dan Sertifikasi Halal Terhadap Customer Loyalty (Studi Kasus pada Produk Skincare Skintific di Kota Malang) - Prasetya, Diva; Pardiman, Pardiman; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this research is to determine the influence of Leadership, Communication, Work Environment on PT Employee Performance. Cimory Plant Pasuruan. The sampling technique used probability sampling to obtain a sample of 70 respondents. The data collection method uses a questionnaire. The data analysis technique used in this research is multiple linear regression. The research results show that Leadership, Communication and Work Environment simultaneously have a positive and significant effect on employee performance. Partially, Leadership and Communication have a positive and significant effect, while the Work Environment and employee performance have a positive and significant effect.  Keywords: Leadership, Communication, Work Environment